Examining the impact of relativism on religious beliefs in postmodern thought: an Islamic perspective - Mohd Khairul Naim Che Nordin (Penerbit Universiti Kebangsaan Malaysia, 2024)
Postmodernism is characterized by a celebration of diversity, difference in viewpoints and a rejection of universal truths. It often critiques the authority of institutions and traditional power structures and emphasizes the subjective nature of human experience. In terms of methodology, postmodernists use deconstruction and analysis of language and discourse to critique and challenge dominant narratives and beliefs. This paper explores the challenges that relativism, as viewed through the lens of postmodernism, poses to the concept of absolute religion. The areas of belief, epistemology, values, and laws are specifically examined. Acceptance of relativism carries significant implications for religion, such as the loss of religion’s exclusive status and the promotion of pluralism - a key goal of postmodernism. A comprehensive literature review is conducted, drawing on the works of philosophers and scholars who have explored the topics of postmodernism and relativism, and their impact on religion. This study seeks to identify the challenges posed by relativism and offer a brief counterargument. The findings suggest that while relativism may recognize the existence of diverse truths and encourage believers to maintain their own beliefs, it ultimately creates problems when it assumes that the fact of truth itself is different and makes the plurality of truth absolute. This leads to skepticism about religion and the view that religion is only individual belief about truth.